2013
DOI: 10.1121/1.4830775
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic droplet vaporization is initiated by superharmonic focusing

Abstract: Acoustically sensitive emulsion droplets composed of a liquid perfluorocarbon have the potential to be a highly efficient system for local drug delivery, embolotherapy or for tumor imaging. The physical mechanisms underlying the acoustic activation of these phase-change emulsions into a bubbly dispersion, termed acoustic droplet vaporization, have not been well understood. The droplets have a very high activation threshold, its frequency dependence does not comply with homogeneous nucleation theory and focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…We infer that that nucleation occurs inside the droplet. This theoretical prediction matches with the high-speed camera observations (Kripfgans et al, 2004;Li et al, 2014;Shpak et al, 2014).…”
Section: Nucleation At a Liquid-liquid Interfacesupporting
confidence: 84%
“…We infer that that nucleation occurs inside the droplet. This theoretical prediction matches with the high-speed camera observations (Kripfgans et al, 2004;Li et al, 2014;Shpak et al, 2014).…”
Section: Nucleation At a Liquid-liquid Interfacesupporting
confidence: 84%
“…Therefore ultrasonically driven bubbles can be used for local application of genes or drugs. This includes employing emulsions of droplets composed of liquid perfluorocarbons, which are acoustically activated to undergo a phase change into a bubbly dispersion, a procedure termed acoustic droplet vaporization [56].…”
Section: Ultrasound Diagnostics Ultrasound Contrast Agents Andmentioning
confidence: 99%
“…Some studies showed that the ADV threshold increases with acoustic frequency [11] , [12] whereas others showed the opposite trend [13] , [14] . While analyzing the experimental observation that the acoustic threshold decreases as the acoustic frequency increases, Shpak et al [15] noted the superharmonic effect that a spherical droplet concentrates an incident acoustic wave at its inner point. Their theoretical analysis showed that the superharmonic focusing effect, triggering the generation of bubbles, increases as the acoustic frequency and the droplet size increase.…”
Section: Introductionmentioning
confidence: 99%